2016
DOI: 10.1155/2016/2954721
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Macroglial Responses in Health and Disease

Abstract: Due to their permanent and close proximity to neurons, glial cells perform essential tasks for the normal physiology of the retina. Astrocytes and Müller cells (retinal macroglia) provide physical support to neurons and supplement them with several metabolites and growth factors. Macroglia are involved in maintaining the homeostasis of extracellular ions and neurotransmitters, are essential for information processing in neural circuits, participate in retinal glucose metabolism and in removing metabolic waste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
129
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 140 publications
(186 reference statements)
3
129
1
1
Order By: Relevance
“…In the human retina, three types of astrocytic cells can be distinguished: (1) Müller cells, damage to which was previously suspected to cause foveal changes in NMOSD in cross-sectional and animal studies,15 16 29 30 (2) elongated retinal astrocytes are located in the RNFL, (3) whereas star-shaped astrocytes reside in the ganglion cell layer 31. Astrocytic dysfunction could lead to neuroaxonal damage in the retina and other affected brain regions, as has been reported in brainstem and chiasm, which was recently also shown in animal models of NMOSD 18 32.…”
Section: Discussionmentioning
confidence: 99%
“…In the human retina, three types of astrocytic cells can be distinguished: (1) Müller cells, damage to which was previously suspected to cause foveal changes in NMOSD in cross-sectional and animal studies,15 16 29 30 (2) elongated retinal astrocytes are located in the RNFL, (3) whereas star-shaped astrocytes reside in the ganglion cell layer 31. Astrocytic dysfunction could lead to neuroaxonal damage in the retina and other affected brain regions, as has been reported in brainstem and chiasm, which was recently also shown in animal models of NMOSD 18 32.…”
Section: Discussionmentioning
confidence: 99%
“…As an important supporting glial cell in the retina, Müller cell abnormal function has been linked to many retinal diseases (de Hoz et al, 2016; Sauter and Brandt, 2016; Wang et al, 2015b; Zhong et al, 2012). We found that ZIKV not only replicates productively in Müller cells but also induces a robust inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Müller cells form an architectural support structure across the whole retina and provide homeostatic and metabolic support to retinal neurons, which are assumedly carried out by astrocytes, oligodendrocytes and ependymal cells in other regions of the CNS (Newman and Reichenbach, 1996; Reichenbach and Bringmann, 2013). Under pathological conditions, Müller cells are activated and produce inflammatory cytokines and growth factors that lead to retinal inflammation, vascular leakage and neuronal degeneration in retinopathies including diabetic retinopathy, age-related macular degeneration and uveitis (de Hoz et al, 2016; Sauter and Brandt, 2016; Wang et al, 2015b; Zhong et al, 2012). Since ZIKV has been detected in cells located in the INL, including those with the morphology of Müller cells (Miner et al, 2016), here, we investigated the effects of ZIKV infection on primary mouse retinal Müller cells.…”
Section: Introductionmentioning
confidence: 99%
“…33 Indeed, it has been recently shown that macroglial cells hypertrophy across the whole retina after an apparently innocuous manipulation such as intravitreal injection of phosphate-buffered saline. 29 It was interesting to find that they also responded to topical administration of bromfenac, as evidenced by the significant increase of GFAP and vimentin and the decrease of CRALBP1 in extracts from intact retinas treated during 7 days with the NSAID.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Macroglial retinal cells, astrocytes, and Müller cells readily respond to intravitreral injections, 29 injury, or disease. [30][31][32][33] A very well characterized model of retinal damage and degeneration is optic nerve axotomy in rodents. [34][35][36][37][38][39] Complete intraorbital optic nerve crush (ONC) is an acute insult that kills the vast majority of retinal ganglion cells (RGCs) within the first 2 weeks after injury.…”
mentioning
confidence: 99%